2004
DOI: 10.1080/1034912042000259242
|View full text |Cite
|
Sign up to set email alerts
|

High School‐Aged Youths' Attitudes Toward their Peers with Disabilities: the role of school and student interpersonal Factors

Abstract: Negative peer attitudes are generally recognised as being a major barrier to full social inclusion at school for children and youth with disabilities. The present study examined the attitudes of 1,872 grade nine high school students in Ontario, Canada toward their peers with disabilities. A bioecological perspective and a structural equation modeling approach were adopted to investigate how various aspects of school culture and student interpersonal factors in¯uenced attitudes. The majority of students (61%) h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
94
2
24

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(131 citation statements)
references
References 36 publications
11
94
2
24
Order By: Relevance
“…Seo and Chen (2009) found that adults who reported favorable attitudes toward individuals with disabilities also reported having greater contact with these individuals. Similar results were found for adolescents (McDougall et al, 2004) and children (Kalyva and Agaliotis, 2009).…”
Section: Teacher Contact With Students With Disabilitiessupporting
confidence: 77%
See 1 more Smart Citation
“…Seo and Chen (2009) found that adults who reported favorable attitudes toward individuals with disabilities also reported having greater contact with these individuals. Similar results were found for adolescents (McDougall et al, 2004) and children (Kalyva and Agaliotis, 2009).…”
Section: Teacher Contact With Students With Disabilitiessupporting
confidence: 77%
“…Previous research supports the notion that increased contact with individuals with disabilities promotes more favorable attitudes toward such individuals in the general population, (Hunt and Hunt, 2000;McDougall et al, 2004;Kalyva and Agaliotis, 2009;Seo and Chen, 2009) as well as with teachers, (Harvey and Green, 1984;Tait and Purdie, 2000). The current study generally supports this notion however; the current results demonstrate that quantity of contact is not the only variable associated with positive attitudes.…”
Section: Discussionsupporting
confidence: 39%
“…14,16,17,21,22,30,32,[34][35][36][37]40,[45][46][47]49 These studies all showed that the more contact children had with people with disabilities, the more positive their attitudes were towards disability. From the nine articles in which effect sizes were available or calculated, effect size d ranged from 0.17 to 2.45 (Table I).…”
Section: Main Results Of Individual Studiesmentioning
confidence: 99%
“…The CATCH was used in full in four studies, 14,[34][35][36] and a subscale was used in one additional study. 37 The 'Attitudes Towards Disabled Persons' 38 scale, or adapted versions of it, was used in four studies. 24,[39][40][41] In addition to self-reported attitude measures, other techniques included asking children questions about how they would respond to a disabled child described in a written vignette.…”
Section: 32mentioning
confidence: 99%
“…Σπγθεθξηκέλα, ζηελ έξεπλα ησλ Hurst et al (2012) βξέζεθε όηη ηα παηδηά πνπ δελ γλώξηδαλ θάπνην άηνκν κε αλαπεξία ζεκείσζαλ ρακειόηεξα επίπεδα απνδνρήο, ζε ζρέζε κε ηα άιια παηδηά πνπ γλώξηδαλ, αλεμαξηήησο κάιηζηα ηεο ζπρλόηεηαο ηεο επαθήο. Σηελ ίδηα θαηεύζπλζε, ζύκθσλα κε ηνπο McDougall, DeWit, King, Miller, & Killip (2004) παξνπζηάζηεθε πςειόηεξνο κέζνο όξνο ζηηο ζεηηθέο ζηάζεηο γηα ηνπο καζεηέο πνπ είραλ θάπνην θίιν ή ζπκκαζεηή κε αλαπεξία. Δπηπξόζζεηα, ζηελ έξεπλα ησλ Rillota θαη Nettelbeck (2007) ζηελ νπνία εθαξκόζηεθε έλα πξόγξακκα επαηζζεηνπνίεζεο θαη γλσξηκίαο κε ηε λνεηηθή πζηέξεζε δηαπηζηώζεθε όηη νη καζεηέο πνπ ζπκκεηείραλ ζην πξόγξακκα ζεκείσζαλ πεξηζζόηεξν ζεηηθέο ζηάζεηο ζπγθξηηηθά κε εθείλνπο πνπ δελ έιαβαλ ηελ αληίζηνηρε παξέκβαζε.…”
Section: η κοινωνική επαφήunclassified